MEDLEM database, a data collection on large Elasmobranchs in the Mediterranean and Black seas - CECILIA MANCUSI; ROMANO BAINO; CATERINA FORTUNA; LUIS GIL DE SOLA; GABRIEL MOREY; MOHAMED NEJMEDDINE BRADAI; ARGYRIOS KALLIANOTIS; ALEN SOLDO; FARID HEMIDA; ADIB ALI SAAD; MARK DIMECH; PANAGIOTA PERISTERAKI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean Large Elasmobranchs Monitoring (MEDLEM) database contains over 3000 records (more than 4000 individuals) of large elasmobranch species from 20 different countries around the Mediterranean and Black seas, observed from 1666 to 2017. The main species included in the archive are the devil fish (1 813 individuals), the basking shark (939 individuals), the blue shark (585 individuals) and the great white shark (337 individuals).In the last decades other species such as the shortfin mako (166 individuals), the spiny butterfly ray (138) and the thresher shark (174 individuals) were reported with an increasing frequency. This was possibly due to an increased public awareness on the conservation status of sharks, and a consequent development of new monitoring programmes. MEDLEM does not have a homogeneous reporting coverage throughout the Mediterranean and Black seas and it should be considered as a database of observed species presence. Scientific monitoring efforts in the south-eastern Mediterranean and Black seas are generally lower than in the northern sectors and the absence in our database of some species does not imply their actual absence in these regions. Some considerations are made on the frequency and spatial distribution of records, size structure of the observed individuals for selected species, general area coverage and species involved as by-catch by fishing gear.

Role of ephemeral vegetation of emerging river bottoms in modulating CO2 exchanges across a temperate large lowland river stretch - Rossano Bolpagni; Silvia Folegot; Alex Laini; Marco Bartoli (Aquatic Sciences, 2017)

Do oxic–anoxic transitions constrain organic matter mineralization in eutrophic freshwater wetlands? - Daniele Longhi; Marco Bartoli; Daniele Nizzoli; Alex Laini; Pierluigi Viaroli (Hydrobiologia, 2016)

Remote sensing of phytoplankton-macrophyte coexistence in shallow hypereutrophic fluvial lakes - Rossano Bolpagni; Mariano Bresciani; Alex Laini; Monica Pinardi; Erica Matta; Eva M. Ampe; Claudia Giardino; Pierluigi Viaroli; Marco Bartoli (Hydrobiologia, 2014)

Benthic respiration and stoichiometry of regenerated nutrients in lake sediments with Dreissena polymorpha - Tomas Ruginis; Marco Bartoli; Jolita Petkuviene; Mindaugas Zilius; Irma Lubiene; Alex Laini; Arturas Razinkovas-Baziukas (Aquatic Sciences, 2014)